Perdarahan Perirenal Spontan pada Pasien dengan Sindrom Antifosfolipid: Laporan Kasus - Adipurnama, William; Oktaviani, Jacinda Risha; Singgih, Nicholas Andrian; Salim, Cecilia Noviyanti; Derry Wendians Suhanto; Manuputty, Egi Edward; Budiawan Atmadja (PT Kalbe Farma Tbk., 2025)
Introduction: Spontaneous perirenal hemorrhage (SPH), also known as Wunderlich syndrome, is a rare condition that can potentially progress into life-threatening non-traumatic retroperitoneal hemorrhage. Common symptoms include acute flank or abdominal pain, a palpable flank mass, and fulminant hypovolemia, collectively referred to as Lenk’s triad, and diagnosis is typically established radiologically using a CT scan. Antiphospholipid syndrome (APS) - a rare, immune-mediated hypercoagulable disorder that occurs in only 5 cases per 100,000 people per year worldwide. It is immune-mediated, characterized by persistent antiphospholipid antibodies (APLA) that cause both arteries and venous thrombosis, and can present as peripheral arterial disease (PAD), acute arterial occlusion, and early atherosclerosis. Case : A 33-year-old woman with chronic kidney disease (CKD) presented with SPH and incidentally diagnosed with peripheral arterial disease (PAD) and APS. Conclusion : Conservative management was beneficial for SPH without the need for surgical intervention; however, antithrombotic therapy for PAD posed additional challenges before the patient was eventually discharged in improved condition for outpatient follow-up.